Early Southern Sports and Sportsmen, 1830-1910 : A Literary Anthology - Rivers, Jacob F., 1951- (Book collections on Project MUSE., 2014)
Early Southern Sports and Sportsmen brings to new readers a wealth of hunting and fishing lore heretofore hard to find by any but scholars in the field of Southern literature. Rivers has gathered a host of well-read and well-heeled sportsmen who relish each and every detail of their encounters with their environment. Sports authors come from every spectrum of Southern society, but their common vocabulary and shared enthusiasm bind them together. Rivers corrects unfortunate stereotypes of hunters as indifferent to aspects of nature other than environmental exploitation. Whether humorists or serious advocates, these authors reveal their sense of their place in the wild, and many advocate ecological good citizenship that disdains wanton slaughter and unethical practices. They condemn such acts as beneath the dignity and honor of true sportsmen. The collection includes accounts of hunting many types of game indigenous to the South from 1830 to 1910, from aristocratic foxhunts to yeoman deer drives. The structure is largely chronological, beginning with John James Audubon's essay on the American wild turkey from his Ornithological Biography (1832) and ending with stories from Alexander Hunter's The Huntsman in the South (1908). Whatever their era, the chief characteristics of these sporting accounts are the excitement the authors experience upon suddenly encountering game, the rigors and hardships they endure in its pursuit, their keen powers of observation of the woods and waters through which they travel and the comedy often found in the strong friendships that frequently mark their adventures. But above all, the tales resonate with a reverence for field sports as the means through which humans establish meaningful and lasting relationships with the mysteries and the magic of nature.